STUDI KOMPOSISI MAKANAN IKAN SEPAT RAWA (Trichogaster trichopterus Pallas) di RAWA TERGENANG DESA MARINDAL KECAMATAN PATUMBAK - Hadi Syahputra; Darma Bakti; Muhammad Riza Kurnia (AQUACOASTMARINE, 2014)
The fresh water in Indonesia has signifikan potential To be exploited as fish cultivation. Food as a component of waters is a ecology factor and have an important role in determining the rate of populations density, population dynamics, growth, reproduction and fish condition. This research aimed to know the composition of three spot gourami’s food ,and broad niche. This research was held on November-December 2013 In Marindal village of Swamp Subdistrict Patumbak, North Sumatera. This study use a grap nets, and fishing trap. The Data analysis was index of the stomach, The frequency of occurrence and niche.The result showed that foods found in fishes intestinal consists of 13 genera Bacillariophyceae, 4 genera Chlorophyceae, 1 genera Conjugatophyceae, 4 genera Coscinodiscophyceae, 3 genera Cyanophyceae,1 genera Euglenophyceae, 1 genera Filosia, 1 genera gastropoda. 1 genera monogonta, dan 1 genera secernentea. The main food is Bacillariophyceae. Chlorophyceae, Cyanophyceae, Conjugatophyceaeas were complements food and Coscinodiscophyceae, Euglenophyceae , Gastropoda, Filosia, Monogonta, Secementea were additives food.Keyword : Swamps, Food composition, Food habits, Trichogaster trichopterus, Patumbak.